A derivative-free method for solving box-constrained underdetermined nonlinear systems of equations - Echebest, Nélida Ester (2012)
A derivative-free iterative method for solving bound-constrained underdetermined nonlinear systems is presented. The procedure consists of a quasi-Newton method that uses the Broyden update formula and a globalized line search that combines the strategy of Grippo, Lampariello and Lucidi with the Li and Fukushima one. Global convergence results are proved and numerical experiments are presented.